Effect of growing pink tomato plants with LED supplementary lighting in a greenhouse covered with diffusion glass on post-harvest fruit quality - Katarzyna Kowalczyk; Małgorzata Mirgos; Anna Sobczak; Jarosław Leon Przybył; Waldemar Kowalczyk; Anna Geszprych; Stanisław Kalisz; Radosław Łaźny; Marek Gajewski; Janina Gajc-Wolska (Acta Scientiarum Polonorum: Hortorum Cultus)
It was found that the taste and quality of tomato fruit can significantly depend on the cultivar, growing conditions, fruit maturity stage, and post-harvest treatments. This study aimed to compare the effects of growing conditions, such as the use of diffusion glass and LED supplementary light (LED+D), with diffusion and standard glass and HPS lamps (HPS+D; HPS) on the quality and post-harvest shelf life of pink tomato fruit cv. ‘Tomimaru Muchoo F1’ in relation to fruit maturity stage and storage temperature. Fruits were harvested at three ripening stages – mature green (MG), breaker (B) and fully ripe (FR). Fruits of each maturity stage were stored under controlled conditions in a cold store at 12 °C for MG and B fruits and at 6 °C for FR fruits (at 85% relative humidity), and 20 °C for all ripening stages (at about 50% relative humidity). Physiological weight loss, dry weight, hardness of fruit, fruit color ( L*, a*, b*, a*/b*), total soluble solids, total sugars, ascorbic acid, titratable acidity, pH, lutein, lycopene, a-carotene, b-carotene were determined. Pink tomato fruits harvested from LED-lighted plants in combination with diffusion glass showed the highest shelf life and post-harvest quality compared to fruits from HPS-lighted plants and HPS-lighted crops in combination with diffusion glass. Stored pink tomato fruits from the LED+D combination were characterized by significantly higher total sugars, vitamin C and β-carotene content than fruits from the combination HPS and HPS+D. Tomato fruits, regardless of the maturity stage, at 20 °C had higher fresh weight loss and lower fruit firmness during storage compared to those stored at lower temperatures. Pink tomato fruits stored in higher temperature colored faster and contained a higher concentration of components such as total soluble solids or ascorbic acid and carotenoids.